Pharmacokinetic Parameters of HIV-1 Protease Inhibitors - Nascimento, André L. C. S.; Fernandes, Richard P. [UNESP]; Quijia, Christian [UNESP]; Araujo, Victor H. S. [UNESP]; Pereira, Juliana; Garcia, Jerusa S.; Trevisan, Marcello G.; Chorilli, Marlus [UNESP] (Wiley, 2020)
Since the beginning of the HIV epidemic, research has been carried out to control the virus. Understanding the mechanisms of replication has given access to the various classes of drugs that over time have transformed AIDS into a manageable chronic disease. The class of protease inhibitors (PIs) gained notice in anti-retroviral therapy, once it was found that peptidomimetic molecules act by blocking the active catalytic center of the aspartic protease, which is directly related to HIV maturation. However, mutations in enzymatic internal residues are the biggest issue for these drugs, because a small change in biochemical interaction can generate resistance. Low plasma concentrations of PIs favor viral natural selection; high concentrations can inhibit even partially resistant enzymes. Food-drug/drug-drug interactions can decrease the bioavailability of PIs and are related to many side effects. Therefore, this review summarizes the pharmacokinetic properties of current PIs, the changes when pharmacological boosters are used and also lists the major mutations to help understanding of how long the continuous treatment can ensure a low viral load in patients.
Keywords: anti-retroviral therapy; drug-drug interactions; pharmacokinetic parameters; protease inhibitors HIV-1; viral resistance